The Spirituality of Language in Cecilia Vicuña’S and Ana María Uribe’S Visual Poetry - Cussen-Abud, F (Routledge, 2022)
We argue that the visual poetic works of the Chilean poet Cecilia Vicuña and the Argentinean poet Ana María Uribe resist traditional expectations for poetry by foregrounding sensual apprehension as a conduit to active readerly involvement in making meaning. Both poets attempt to eliminate the boundaries between spirit and reality by emphasizing that the immanence, or ‘spirit’, of language paradoxically resides in its materiality and is actualized in the relational (in the reading and writing process). Our theoretically informed readings of their poems illustrate that this ‘spirit’ exists as a continuous self-organization that allows for a democratic poeisis. © 2022 Bulletin of Spanish Studies.